LAS CONSIGNAS DE CENSURA DE TEMA DEPORTIVO EN LA PRENSA ESPAÑOLA DEL PRIMER FRANQUISMO: UN ESTUDIO DOCUMENTAL - Dr. Alejandro VIUDA-SERRANO (Fonseca, Journal of Communication, 2023)
This study seeks to be an initial documentary analysis on State orders to the press about sport during the first part of Franco regime. Basic tools of the State to control media and use them to inculcate the values of the new regime were such orders. Using historiographical research, we will check a large amount of unpublished primary documents collected in the Archivo General de la Administración to explain the context and development of sports censorship throughout the period covered by the study.